A study with a purpose to determine structural defects and faults: The seismic risks of the existing buildings in various districts of Istanbul/Turkey - Kocak, Ali (ACADEMIC JOURNALS, 2010)
Istanbul, a host of many different civilizations-being a city of tourism, art, and culture, with a megacity area of 5712 km(2), having more than 1,000,000 buildings with a population exceeding 10 million, has been exposed to numerous earthquakes in its history and, has experienced damaged extensively as a result of these earthquakes. Istanbul was also affected by the recent August 17th Golcuk and November 12th Duzce Earthquakes; and approximately 32,637 buildings were damaged. When the regional earthquake accelerations were examined, it was observed not even a design earthquake had occurred in Istanbul as a result of these earthquakes. On the other hand, damage, destruction, and the losses of life were observed to be more than the expected values. As one can comprehend from these figures, it can be stated that the building stock of Istanbul is defective; and these buildings contain the risk of severe damage or total collapse. It is considerably significant to repair these negativities in the defective buildings and remove the apparent defects for minimizing the risks. Moreover, it was pointed out that a great danger awaits Istanbul and the Marmara Region because of the seismic risk and structural damage scenarios. Consequently, the investigation of the present building stock of Istanbul would help for better determination of earthquake scenarios for Istanbul and the Marmara Region. A detailed examination was conducted on a total of 467 buildings with reinforced concrete or masonry structural systems, from 23 different districts of Istanbul, and the results obtained were evaluated in this study. The damage conditions of the buildings, their suitability to the original project, concrete strength values, reinforcement conditions, project and building defects, and other architectural and structural system faults, not suitable as regards to the seismic design, were determined. As a result, apparent defects and faults for the investigated buildings were marked.
Keywords: Earthquake; present building stock; structural defects; risk analysis; Marmara region; REINFORCED-CONCRETE STRUCTURES; MARMARA SEA REGION; TURKEY; DAMAGE; Science & Technology - Other Topics